A serial mediation model of the relationship between alexithymia and BMI: The role of negative affect, negative urgency and emotional eating. (1st February 2019) - Pink, Aimee E.; Lee, Michelle; Price, Menna; Williams, Claire
Abstract: Difficulty identifying and describing emotions (alexithymia) has been related to impulsiveness and negative affect, emotional eating and obesity. However, previous research findings concerning the relationship between alexithymia and obesity have been mixed and inconsistent, raising the possibility that the relationship is indirect and mediated by multiple unknown factors. The aim of the study was to comprehensively explore the potential pathways between alexithymia and obesity via a novel theoretical model, and for the first time, incorporate negative affect, impulsiveness (negative urgency) and emotional eating as potential mediating factors. Two questionnaire-based studies were conducted; the first as an exploratory analysis within a student sample ( N = 125), and the second as a self-replication within a more representative general population sample ( N = 342). Study One revealed that difficulty identifying feelings predicted Body Mass Index (BMI) both directly ( B = 0.1694, CI = 0.0194-0.3194) and indirectly via negative urgency and emotional eating ( B = 0.0074, CI = 0.0001-0.0315). In contrast, Study Two revealed that alexithymia predicted BMI indirectly via negative affect (when depression was included in the model; B = 0.0335, CI = 0.0019-0.0660) or negative urgency (when anxiety was included in the model; B = 0.0021, CI = 0.0001-0.0066). Our findings provide partial support for the hypothesised model and offer original insight into the relationship between alexithymia and obesity. Additionally, our findings highlight important methodological considerations for future research and suggest that ways to address an individual's ability to identify, describe and regulate emotions should be considered when designing interventions to assist weight loss and management.